The results of a 24-month controlled, prospective study of relapsing multiple sclerosis patients at risk for progressive multifocal encephalopathy, who switched from prolonged use of natalizumab to teriflunomide. Issue 4 (October 2021) - Cohan, Stanley; Gervasi-Follmar, Tiffany; Kamath, Aneesh; Kamath, Vineetha; Chen, Chiayi; Smoot, Kyle; Baraban, Elizabeth; Edwards, Keith
Background: Natalizumab (NTZ) is a highly effective disease modifying treatment for relapsing multiple sclerosis (RMS), but it increases risk of progressive multifocal leukoencephalopathy (PML) in patients with serum anti- John Cunningham virus (JCV) antibodies. Objective: To assess the safety and efficacy of rapid transition, from NTZ to teriflunomide (TFM) in RMS patients. Methods: Clinically stable NTZ-treated, anti-JCV antibody positive RMS patients were switched to TFM 28 ± 7 days after their last dose of NTZ. The primary endpoint was proportion of relapse free patients at 24 months. Results: Median [IQR] age of the 55 enrolled patients was 47 [40.7, 56.3] years, 76% were female. The median [IQR] number of prior NTZ treatments was 34 [18, 64]. annualized relapse rate (ARR) was 0.07 and 77% of the patients were relapse free at 24 months. Mean time to first GAD + lesion was 19.6 months, and to new/enlarging T2 lesion was 19.2 months. Mean time to 3 month sustained disability worsening (SDW) was 22 months and proportion free of 3-month SDW was 0.87. There were no cases of PML. Conclusions: The washout-free transition of NTZ to TFM was an efficacious and safe strategy for patients at risk of developing PML. ClinicalTrials.gov Identifier: NCT01970410